Taxonomic study of Pteris tripartita and P. wallichiana (Pteridaceae) from India - Das, Piu; Mazumdar, Jaideep (Phytotaxa, 2019)
Detailed morphological features and images are presented for Pteris tripartita and P. wallichiana from India, which are often misidentified and confused. Based on field observation and study of specimens, the hairy form of P. wallichiana was accepted as a distinct variety, not a synonym of P. wallichiana. The nomenclatural status of P. wallichiana was clarified. Lectotypes were selected for P. tripartita and P. wallichiana var. yunnanensis.